Laminate and method for manufacturing a laminate

JP2026165657APending Publication Date: 2026-10-14TOYO INK MFG CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
JP2025058156
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2025-03-31
Publication Date
2026-10-14

Smart Images

  • Figure 2026165657000001
    Figure 2026165657000001
  • Figure 2026165657000002
    Figure 2026165657000002
  • Figure 2026165657000003
    Figure 2026165657000003
Patent Text Reader

Abstract

The present invention aims to provide a laminate with a functional layer that has excellent dead-hold properties and can be used in packaging materials with folds. [Solution] A laminate having, in order, at least a paper substrate, an anchor coat layer, and a functional layer (excluding the ink layer), The functional layer is at least one selected from the group consisting of a barrier layer, an oil-resistant layer, a water-repellent layer, and a water-resistant layer, and the functional layer comprises resin (I). A laminate in which the breaking strength of the functional layer measured under the following condition (1) is less than 8 MPa. Condition (1): In accordance with JIS K 6251:2023, a dumbbell-shaped test specimen of type 3 with a thickness of 0.3 m and a width of 5 mm is prepared, a tensile test is performed at a tensile speed of 50 m / min, the load at fracture [N] is measured, and the fracture strength is calculated using the following formula 1. (Equation 1) Breaking strength [MPa] = (Load at break [N]) / (Cross-sectional area of ​​the test specimen [mm²]) 2 ])
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] The present invention relates to a laminate and a method for producing the laminate. BACKGROUND ART

[0002] Packaging materials using a paper base material are used in applications such as foods, sanitary products, and daily necessities as laminates having functional layers such as a gas barrier layer and an oil-resistant layer according to the intended use.

[0003] For example, Patent Document 1 discloses a laminate having a paper base material / folding-resistant layer / functional layer, wherein by setting the elongation of the folding-resistant layer to 200% or more and the recovery rate to 80% or more, the laminate can suppress functional deterioration during bending. PRIOR ART DOCUMENTS PATENT DOCUMENTS

[0004] PATENT DOCUMENT 1 Japanese Patent No. 7588264 SUMMARY OF THE INVENTION PROBLEM TO BE SOLVED BY THE INVENTION

[0005] However, since conventional laminates use a folding-resistant layer with a recovery rate of 80% or more, there is a problem that creases cannot be retained when producing packaging materials with creases (hereinafter referred to as dead hold property).

[0006] An object of the present invention is to provide a laminate with a functional layer that has excellent dead hold property and can be used for creased packaging materials. EFFECTS OF THE INVENTION

[0007] According to the present invention described above, it is possible to provide a laminate with a functional layer that has excellent dead hold property and can be used for creased packaging materials. Further, the present invention can provide a method for producing the laminate. MEANS FOR SOLVING THE PROBLEM

[0008] The laminate of the present invention sequentially comprises at least a paper substrate, an anchor coat layer, and a functional layer (excluding the ink layer). The functional layer is at least one selected from the group consisting of a barrier layer, an oil-resistant layer, a water-repellent layer, and a water-resistant layer, and the functional layer comprises resin (I). The tensile strength of the aforementioned functional layer, measured under the following condition (1), is less than 8 MPa. Condition (1): In accordance with JIS K 6251:2023, a dumbbell-shaped test specimen of type 3 with a thickness of 0.3 m and a width of 5 mm is prepared, a tensile test is performed at a tensile speed of 50 m / min, the load at fracture [N] is measured, and the fracture strength is calculated using the following formula 1. (Equation 1) Breaking strength [MPa] = (Load at break [N]) / (Cross-sectional area of ​​the test specimen [mm²]) 2 ]) [Modes for carrying out the invention]

[0009] Embodiments of the present invention will be described in detail below. The embodiments or requirements described below are examples of embodiments of the present invention, and the present invention is not limited to these as long as it can solve the problem. In addition, in the following description, "various properties" of the functional layer refer to at least one of the following functions: water vapor barrier properties, oxygen barrier properties, oil resistance, water resistance, and water repellency.

[0010] The laminate of the present invention sequentially comprises at least a paper substrate, an anchor coat layer, and a functional layer (excluding the ink layer). The functional layer is at least one selected from the group consisting of a barrier layer, an oil-resistant layer, a water-repellent layer, and a water-resistant layer, and the functional layer comprises resin (I). The tensile strength of the aforementioned functional layer, measured under the following condition (1), is less than 8 MPa. Condition (1): In accordance with JIS K 6251:2023, a dumbbell-shaped test specimen of type 3 with a thickness of 0.3 m and a width of 5 mm is prepared, a tensile test is performed at a tensile speed of 50 m / min, the load at fracture [N] is measured, and the fracture strength is calculated using the following formula 1. (Equation 1) Breaking strength [MPa] = (Load at break [N]) / (Cross-sectional area of ​​the test specimen [mm²]) 2 ])

[0011] The mechanism by which the laminate of the present invention can solve the problem is hypothesized as follows. The laminate of the present invention comprises a paper substrate, an anchor coat layer, and a functional layer in that order, wherein the functional layer is characterized by a breaking strength of less than 8 MPa. When the laminate is bent, if paper fibers in the paper substrate protrude and pressure is applied to the functional layer, they may pierce the functional layer, making it prone to cracking. However, since the functional layer has a breaking strength of less than 8 MPa and possesses appropriate flexibility, cracking can be suppressed. Furthermore, because the breaking strength is less than 8 MPa, the coating is not too hard. It is presumed that this results in a laminate with good dead-hold properties.

[0012] The following are examples of the configuration of the laminate of the present invention. Needless to say, the laminate is not limited to the following configuration. In the configuration notations (1) to (12) below, " / " indicates the boundary of each layer. The adhesive layer only needs to have the function of bonding each layer, and includes embodiments in which a thermoplastic resin such as polyolefin resin used in extrusion lamination is used in addition to adhesives used in dry lamination and non-sol lamination. Furthermore, the heat seal layer includes embodiments in which it is formed from a coating agent and a sealant film. (1) Paper substrate / Anchor coat layer / Functional layer (2) Paper substrate / Ink layer / Anchor coat layer / Functional layer (3) Paper substrate / Anchor coat layer / Ink layer / Functional layer (4) Paper substrate / Anchor coat layer / Functional layer / Ink layer (5) Heat seal layer / Paper substrate / Anchor coat layer / Functional layer (6) Heat seal layer / Paper substrate / Ink layer / Anchor coat layer / Functional layer (7) Heat seal layer / Paper substrate / Anchor coat layer / Ink layer / Functional layer (8) Heat seal layer / Paper substrate / Anchor coat layer / Functional layer / Ink layer (9) Heat seal layer / adhesive layer / paper substrate / anchor coat layer / functional layer (10) Heat seal layer / Adhesive layer / Paper substrate / Ink layer / Anchor coat layer / Functional layer (11) Heat seal layer / Adhesive layer / Paper substrate / Anchor coat layer / Ink layer / Functional layer (12) Heat seal layer / Adhesive layer / Paper substrate / Anchor coat layer / Functional layer / Ink layer

[0013] [Functional Layer] In this specification, the functional layer is a layer for imparting various functions to a paper substrate and does not include an ink layer. By having a functional layer, the laminate can obtain various functions, a functional layer appearance, and deadhold properties. The breaking strength of the functional layer is characterized by being less than 8 MPa. The breaking strength of the functional layer is preferably 0.1 to 8 MPa, more preferably 0.5 to 5 MPa, and even more preferably 1 to 3 MPa. When the functional layer is within the above range, cracking of the functional layer, which leads to a decrease in functionality, is suppressed when the layer is folded, resulting in a good appearance of the functional layer and a laminate with even better deadhold properties. Furthermore, the breaking strain of the functional layer is preferably 200% or more, more preferably 250 to 800%, and even more preferably 300 to 500%. When the breaking strain of the functional layer is within the above range, the appearance of the functional layer and deadhold properties are further improved.

[0014] <Method for measuring fracture strength> In accordance with JIS K 6251:2023, a dumbbell-shaped test specimen of type 3 with a thickness of 0.3 m and a width of 5 mm was prepared, and a tensile test was conducted at a tensile speed of 50 m / min. The load at fracture [N] was measured, and the fracture strength was calculated using the following formula 1. Equation 1: Breaking strength [MPa] = (Load at break [N]) / (Cross-sectional area of ​​the test specimen [mm²]) 2 ]) <Method for measuring fracture strain> In accordance with JIS K 6251:2023, a dumbbell-shaped test specimen of type 3 with a thickness of 0.3 m and a width of 5 mm was prepared, and a tensile test was conducted at a tensile speed of 50 m / min. The load at fracture [N] was measured, and the fracture strength was calculated using the following formula 3. Equation 3: Fracture strain [%] = {(gauge length at fracture) - (gauge length before tensile test)} / (gauge length before tensile test) × 100 Gauge markings distance before tensile test [mm]: 20 mm

[0015] The functional layer contains resin (I). From the viewpoint of functionality, appearance of the functional layer, and dead-hold properties, resin (I) preferably contains at least one selected from the group consisting of urethane resin (A), acrylic resin (B), styrene elastomer resin (C), and polysaccharide resin (D). The coating amount of the functional layer is 0.5 to 15 g / m². 2 Preferably, 1.0 to 12 g / m 2 More preferably, 1.5-10 g / m 2 A more preferable option is a coating amount of 0.5 g / m² for the functional layer. 2 At this level, the various performance aspects and appearance of the functional layer are further improved. 2 The deadholding ability improves further at the following point.

[0016] The functional layer is preferably at least one layer selected from the group consisting of barrier layers such as water vapor barrier layers and oxygen barrier layers, oil-resistant layers, water-resistant layers, and water-repellent layers. Among these, water vapor barrier layers and oil-resistant layers are more preferred.

[0017] <Urethane resin (A)> Examples of urethane resins (A) include polyurethane resins synthesized from polyols and polyisocyanates, and polyurethane resins obtained as reaction products of a urethane prepolymer of terminal isocyanates synthesized from polyols and polyisocyanates with a polyamine. Examples of synthesis methods include the method described in Japanese Patent Application Publication No. 2013-256551.

[0018] The urethane resin (A) preferably contains units derived from polyols. Examples of polyols include polyether polyols, polyester polyols, and polycarbonate polyols. Among these, polyether polyols and polyester polyols are preferred. The content of units derived from polyols is preferably 5 to 80% by mass, more preferably 10 to 60% by mass, and even more preferably 10 to 50% by mass, based on 100% by mass of the urethane resin.

[0019] The weight-average molecular weight of the urethane resin (A) is preferably 10,000 to 100,000, and more preferably 10,000 to 80,000. When the weight-average molecular weight of the urethane resin (A) is within the above range, the appearance of the functional layer and the dead-hold properties are further improved. The glass transition temperature of the urethane resin (A) is preferably 20°C or lower, more preferably -60°C to 0°C, and even more preferably -40°C to -5°C. When the glass transition temperature of the urethane resin (A) is within the above range, the appearance of the functional layer and the dead-hold properties are further improved. The urethane resin (A) is preferably a resin having an amine value. The amine value of the urethane resin is preferably 0.5 to 30 mgKOH / g, and more preferably 1 to 20 mgKOH / g. When the amine value of the urethane resin (A) is within the above range, the appearance of the functional layer is further improved. In addition, the urethane resin (A) is preferably a resin having a hydroxyl value. The hydroxyl value of the urethane resin is preferably 0.5 to 30 mg KOH / g, and more preferably 1 to 20 mg KOH / g. When the hydroxyl groups of (A) of the urethane resin are within the above range, the appearance of the functional layer is further improved.

[0020] <Acrylic resin (B)> Acrylic resin (B) is a resin having units derived from acrylic monomers. Acrylic resin (B) may further have units derived from styrene monomers and units derived from maleic acid monomers. Acrylic resin (B) is preferably a resin having carboxyl groups. This allows acrylic resin (B) to be used as an aqueous resin.

[0021] Examples of acrylic monomers include alkyl (meth)acrylates, alkyl (meth)acrylates, and hydroxyalkyl (meth)acrylates. The alkyl group constituting the alkyl esters preferably has 1 to 18 carbon atoms. Examples of acrylic monomers include acrylic acid esters and methacrylic acid esters. Examples of acrylic acid esters include methyl acrylate, ethyl acrylate, propyl acrylate, butyl acrylate, hexyl acrylate, 2-ethylhexyl acrylate, cyclohexyl acrylate, benzyl acrylate, dimethylaminoethyl acrylate, hydroxyethyl acrylate, hydroxypropyl acrylate, and glycidyl acrylate. Examples of methacrylic acid esters include methyl methacrylate, ethyl methacrylate, propyl methacrylate, butyl methacrylate, hexyl methacrylate, 2-ethylhexyl methacrylate, and cyclohexyl methacrylate. Examples of acrylic monomers other than those listed above include benzyl (meth)acrylate, dimethylaminoethyl (meth)acrylate, hydroxyethyl (meth)acrylate, hydroxypropyl (meth)acrylate, glycidyl (meth)acrylate, acrylic acid, methacrylic acid, crotonic acid, maleic anhydride, fumaric acid, itaconic acid, etc.

[0022] Examples of the styrene monomers mentioned above include styrene, α-methylstyrene, o-methylstyrene, p-methylstyrene, and m-methylstyrene. Examples of maleic acid monomers include maleic anhydride and maleic acid.

[0023] If the acrylic resin (B) contains carboxyl groups, it can be neutralized with a basic compound to make it aqueous. Note that "making it aqueous" means modifying it into a water-soluble resin or emulsion. Basic compounds include, for example, amine compounds and alkali metals. Examples of the above-mentioned amine compounds include ammonia; alkylamines such as diethylamine, triethylamine, and ethylenediamine; and alkanolamines such as monoethanolamine, ethylethanolamine, diethylethanolamine, diethanolamine, and triethanolamine. Examples of the above-mentioned alkali metals include sodium hydroxide and potassium hydroxide. These can be used individually or in combination of two or more.

[0024] The acid value of the acrylic resin (B) is preferably 10 to 300 mg KOH / g, more preferably 15 to 300 mg KOH / g, and even more preferably 15 to 250 mg KOH / g. When the acid value of the acrylic resin (B) is within the above range, the appearance of the functional layer and the dead-holding properties are further improved. The glass transition temperature of the acrylic resin (B) is preferably -20 to 150°C, and more preferably -10 to 130°C. When the glass transition temperature of the acrylic resin (B) is within the above range, the appearance of the functional layer and the dead-holding properties are further improved. Furthermore, the weight-average molecular weight of the acrylic resin (B) is preferably 5,000 to 700,000, more preferably 8,000 to 500,000, and even more preferably 8,000 to 200,000. When the weight-average molecular weight of the acrylic resin (B) is within the above range, the appearance of the functional layer and the dead-holding properties are further improved.

[0025] Examples of commercially available acrylic resins (B) include the Joncryl series from BASF Japan and the SEIKOAT series from Seikoh PMC, such as SEIKOAT NE-2260 (styrene acrylic emulsion, manufactured by Seikoh PMC), Joncryl HPB1631 (modified styrene acrylic emulsion, manufactured by BASF Japan), and SEIKOAT PE-2273 (acrylic emulsion, manufactured by Seikoh PMC).

[0026] <Styrene elastomer resin (C)> Styrene elastomer resins (C) consist of polystyrene blocks and rubber intermediate blocks. The polystyrene portion forms physical crosslinks (domains) to act as crosslinking points, while the intermediate rubber blocks provide rubber elasticity. The rubber intermediate blocks include polybutadiene (B), isobutylene (IB), polyisoprene (I), and polyolefin elastomers (ethylene-propylene, EP). Depending on the arrangement pattern with the hard segment polystyrene (S), they are classified into linear and radical types. Examples of styrene elastomer resins (C) include styrene-isobutylene-styrene copolymer (SIBS), styrene-isoprene-styrene block copolymer (SIS), hydrogenated styrene-ethylene-propylene-styrene block copolymer (SEPS), styrene-butylene-styrene block copolymer (SBS), hydrogenated styrene-ethylene-butylene-styrene block copolymer (SEBS), styrene-butadiene-isoprene-styrene block copolymer (SBIS) or hydrogenated styrene-butadiene-isoprene-styrene block copolymer (SEEPS), styrene-butadiene copolymer (SB), and their acid-modified, acid anhydride-modified, amine-modified, and the like. Examples of commercially available styrene elastomer resins (C) include Tefabloc SJ5400B and SJ6400B from Mitsubishi Chemical Corporation, TF-A30NT, TF-A40NT, and TF-A50NT from Aron Kasei Co., Ltd., SEPTON2005, SEPTON4033, SEPTON4033, and SEPTON8004 from Kuraray Co., Ltd., Asapren T-432, ToughTec H1053, ToughTec H1051, and ToughTec M1981 from Asahi Kasei Corporation, and SIBSTAR103T from Kaneka Corporation.

[0027] The content of styrene-derived units in the styrene elastomer resin (C) is preferably 10 to 50% by mass, and more preferably 10 to 30% by mass, out of 100% by mass of all units. When the content of styrene-derived structures in the styrene elastomer resin (C) is within the above range, the appearance of the functional layer and the dead-hold properties are further improved.

[0028] <Polysaccharide resin (D)> Polysaccharide resins (D) are high-molecular-weight compounds formed by the bonding of numerous monosaccharides such as glucose. Examples of polysaccharide resins (D) include starch-based resins, cellulose resins, chitin, alginic acid, pectin, glucomannan, galactomannan, hyaluronic acid, fucoidan, agarose, carrageenan, dextran, glucan, and inulin. Among these, starch-based resins are preferred from the viewpoint of oxygen barrier properties.

[0029] <Starch-based resin> The starch used as a raw material for starch-based resins can be unmodified starch or chemically modified starch. Of these, chemically modified starch is more preferred from the viewpoint of viscosity stability of the coating agent. Examples of starch include wheat starch, corn starch, tapioca starch, potato starch, cassava starch, pea starch, oat starch, arrowroot starch, and rice starch. Of these, corn starch, tapioca starch, cassava starch, and potato starch are preferred.

[0030] Starch-based resins are preferably used after being dissolved in water. The dissolution process preferably includes a plasticizer in addition to water. Examples of plasticizers include polyol-based, phthalate-based, trimellitic acid-based, and epoxy-based plasticizers. Among these, polyol-based plasticizers are preferred because they improve bending resistance.

[0031] The resin (I) content in the functional layer is preferably 60 to 90% by mass, and more preferably 60 to 80% by mass, based on 100% by mass of the functional layer. When the resin content in the functional layer is within the above range, the oxygen barrier properties, the appearance of the functional layer, and the deadhold properties are further improved.

[0032] <Other resins> The functional layer may contain "other resins" other than resin (I). These other resins are not particularly limited, but examples include polyvinyl alcohol-based resins (including ethylene vinyl alcohol-based resins), styrene-maleic acid resins, polylactic acid resins, and modified resins thereof. These other resins may be used individually or in combination of two or more.

[0033] The total resin content in the functional layer is preferably 60 to 100% by mass, and more preferably 70 to 90% by mass, of 100% by mass of the functional layer. When the resin content in the functional layer is within the above range, the various performance characteristics of the functional layer, the appearance of the functional layer, and the deadhold properties are further improved.

[0034] <Additives included in the functional layer> The functional layer may contain additives. Examples of additives include hydrocarbon waxes, inorganic fillers, organic fillers, silane coupling agents, titanate coupling agents, flame retardants, preservative stabilizers, antioxidants, metal deactivators, UV absorbers, thixotropy imparters, leveling agents, defoamers, dispersion stabilizers, fluidity imparters, and colorants. Liquid rubber or softeners may also be included to improve fluidity and adhesion. In particular, from the viewpoint of improving the various performance aspects of the functional layer, the appearance of the functional layer, and the deadhold properties, it is preferable to include hydrocarbon waxes and / or inorganic fillers.

[0035] <Hydroxide-based waxes> The functional layer preferably contains a hydrocarbon wax. The inclusion of a hydrocarbon wax in the functional layer further improves various functionalities such as water vapor barrier properties, oil resistance, water resistance, and water repellency, as well as the appearance of the functional layer and its deadhold properties. The hydrocarbon wax used in this invention refers to an organic substance mainly composed of a long-chain alkyl group skeleton, which is solid at room temperature and becomes liquid when heated, and may contain acid groups, ester groups, hydroxyl groups, etc., within its skeleton.

[0036] Hydrocarbon waxes can be classified into natural waxes and synthetic waxes. Examples of hydrocarbon waxes include paraffin wax, microcrystalline wax, ozokerite, ceresin, candelilla wax, and beeswax. Among commercially available hydrocarbon waxes, natural waxes include paraffin wax and microcrystalline wax manufactured by Nippon Seiro Co., Ltd. and ENEOS Corporation. Furthermore, synthetic waxes include FT115, FT0165, SX105, and FNP0090 from Nippon Seiro Co., Ltd., CERAMER polymer, POLYWAX polyethylene, UNICID carboxylic acid, UNILIN alcohol, UNITHOX ethoxylate, PETROLITE copolymer, and VYBAR polymer from Baker Hughes Corporation, and Diacarna from Mitsubishi Chemical Corporation, and the Sunwax series and Viscol series from Sanyo Chemical Corporation. Furthermore, the hydrocarbon waxes of the present invention also include oxidized waxes synthesized from these raw materials through reactions such as oxidation, saponification, esterification, maleation, and acid anhydride formation, as well as blended waxes obtained by incorporating these into resins, and emulsion waxes obtained by dispersing these waxes in water.

[0037] The hydrocarbon wax content is preferably 5 to 80% by mass, and more preferably 8 to 50% by mass, of 100% by mass of the functional layer. When the hydrocarbon wax content in the functional layer is within the above range, the water vapor barrier properties, oil resistance, water resistance, water repellency, appearance of the functional layer, and dead hold properties are further improved. Furthermore, the mass ratio of resin to hydrocarbon wax in the functional layer is preferably 9:1 to 5:5, and more preferably 8:2 to 6:4. When the mass ratio of resin to hydrocarbon wax in the functional layer is within the above range, the water vapor barrier properties, oil resistance, water resistance, water repellency, appearance of the functional layer, and dead hold properties are further improved.

[0038] <Inorganic filler> The functional layer preferably further contains an inorganic filler. The inclusion of an inorganic filler further improves the various performance characteristics, appearance, and deadhold properties of the functional layer. Examples of inorganic fillers include inorganic layered fillers such as montmorillonite, calcium carbonate, talc, titanium dioxide, aluminum oxide, barium sulfate, zirconium silicate, and silica. Among these, inorganic layered fillers are preferred from the viewpoint of improving oxygen barrier properties. <Inorganic layered filler> Inorganic layered fillers are inorganic fillers in which single crystal layers overlap to form a layered structure, and those that swell and / or cleave in a solvent are particularly preferred. The volume-average particle thickness of the inorganic layered filler is preferably 0.05 to 30 nm, more preferably 0.1 to 10 nm, and even more preferably 0.5 to 3 nm. The volume-average particle diameter of the inorganic layered filler is preferably 0.01 to 5 μm, more preferably 0.05 to 3 μm, and even more preferably 0.1 to 1 μm. In addition, the volume-average particle aspect ratio of the inorganic layered filler is preferably 10 to 2,000, more preferably 100 to 1,000, and even more preferably 300 to 700. In this invention, the particle thickness, particle diameter, and particle aspect ratio of the inorganic layered filler can be measured using an atomic force microscope (AFM).

[0039] Inorganic layered fillers include, for example, montmorillonite, beiderite, saponite, hectorite, souconite, vermiculite, mica, paragonite, lepidolite, margalite, clintonite, anandite, chlorite, donbasite, sudoite, cuqueite, clinochlore, chamosite, nimite, tetrasilyl mica, talc, pyrophyllite, nacrite, kaolinite, halloysite, chrysotile, sodium teniolite, xanthophyllite, antigorite, dicite, hydrotalcite, etc., and it is preferable that one or more are selected from the group consisting of kaolin, montmorillonite, and mica, with montmorillonite being more preferable. Montmorillonite possesses both high water absorption due to its layered structure and high viscosity after swelling.

[0040] The average particle diameter of the inorganic filler measured by the laser scattering method is preferably 5 μm or less, more preferably 1 μm or less, still more preferably 0.5 μm or less, and particularly preferably 0.01 to 0.1 μm. When the average particle diameter of the inorganic filler is within the above range, the appearance of the functional layer and the dead hold property are further improved. The specific surface area of the inorganic filler is 10 to 100 m 2 / g, more preferably 10 to 80 m 2 / g. When the specific surface area of the inorganic fine particles is within the above range, the appearance of the functional layer and the dead hold property are further improved.

[0041] The content of the inorganic filler in the functional layer is preferably 1 to 40% by mass, more preferably 10 to 35% by mass, and still more preferably 20 to 30% by mass, based on 100% by mass of the functional layer. When the content of the inorganic filler is within the above range, various performances of the functional layer, the appearance of the functional layer, and the dead hold property are further improved. The mass ratio of the resin to the inorganic filler in the functional layer is preferably 4:6 to 9:1, more preferably 6:4 to 8:2, and still more preferably 8:2 to 7:3. When the non-volatile content ratio of the resin to the inorganic filler in the functional layer is within the above range, various performances of the functional layer, the appearance of the functional layer, and the dead hold property are further improved.

[0042] <Method for Forming Functional Layer> In the present invention, examples of the method for forming the functional layer include a method of applying a functional coating agent and then drying it, a method of melt-coating the resin and the like contained in the functional layer, and the like. Examples of the form of the functional coating agent include a solution type and a hot-melt type.

[0043] <Functional Coating Agent> The functional coating agent is obtained by uniformly mixing the resin (I) and, if necessary, a solvent and / or an additive using a mixing method described later. Examples of the above mixing method include stirrers such as planetary mixers and dispersers, and dispersing machines such as ball mills, bead mills, roller mills, pebble mills, attritors, and sand mills.

[0044] <Case where Functional Layer is Water Vapor Barrier Layer> One of the functional layers is the water vapor barrier layer. The water vapor barrier layer has a water vapor transmission rate of 200 g / m³ as measured by JIS Z0208:1976 (Cup method) Method B (temperature 40°C ± 0.5°C, relative humidity 90% ± 2%). 2 The layer is less than 1.5 days. The method for forming the water vapor barrier layer can utilize the embodiments and preferred forms of the <Method for Forming a Functional Layer> described above, and among these, a layer formed by applying and drying a water vapor barrier coating agent is preferred. The water vapor barrier coating agent can utilize the embodiments and preferred forms of the <Functional Coating Layer> described above. The amount of water vapor barrier layer to be applied is not particularly limited, but in a dry state, it is 0.5 to 15 g / m². 2 Preferably, 1.0 to 12 g / m 2 More preferably, 1.5-10 g / m 2 A more preferable amount for the water vapor barrier layer is 0.5 g / m². 2 As a result of meeting the above criteria, the water vapor barrier properties and the appearance of the functional layer are good, and the density is 15 g / m². 2 The following conditions result in good dead-hold performance. The rupture strength of the water vapor barrier layer is less than 8 MPa, preferably 0.1 MPa or higher, more preferably 0.5 to 5 MPa, and even more preferably 1 to 3 MPa. Having the functional layer within the above range improves the appearance and deadhold properties of the functional layer.

[0045] The water vapor barrier layer contains a resin (I), which comprises at least one selected from the group consisting of urethane resins (A), acrylic resins (B), styrene elastomer resins (C), and polysaccharide resins (D). Among these, acrylic resins (B) and styrene elastomer resins (C) are preferred. When the water vapor barrier layer contains the above resin (I), the water vapor barrier properties, the appearance of the functional layer, and the deadhold properties are further improved. The water vapor barrier layer preferably comprises at least one material selected from the group consisting of urethane resin (A), acrylic resin (B), and styrene elastomer resin (C), and a hydrocarbon wax such as paraffin wax. When the water vapor barrier layer is a combination of the above materials, the water vapor barrier properties, the appearance of the functional layer, and the deadhold properties are further improved.

[0046] The content of resin (I) is preferably 60 to 95% by mass, and more preferably 70 to 90% by mass, of 100% by mass of the water vapor barrier layer. When the resin content in the water vapor barrier layer is within the above range, the water vapor barrier properties, the appearance of the functional layer, and the dead hold properties are further improved.

[0047] The hydrocarbon wax content is preferably 5 to 80% by mass, and more preferably 8 to 50% by mass, of 100% by mass of the water vapor barrier layer. When the hydrocarbon wax content in the water vapor barrier layer is within the above range, the water vapor barrier properties, the appearance of the functional layer, and the dead hold properties are further improved. Furthermore, the non-volatile content ratio of the resin to the hydrocarbon wax in the water vapor barrier layer is preferably 9:1 to 5:5, and more preferably 8:2 to 6:4. When the non-volatile content ratio of the resin to the hydrocarbon wax in the water vapor barrier layer is within the above range, the water vapor barrier properties, the appearance of the functional layer, and the dead hold properties are further improved.

[0048] <When the functional layer is an oxygen barrier layer> An example of a functional layer used in the present invention is an oxygen barrier layer. This oxygen barrier layer was measured using a method compliant with JIS K 7126-2:2006, under measurement conditions of 23°C and 90% RH, and the measured oxygen permeability was 200 g / m³. 2 The layer is less than 24 hours old. The method for forming the oxygen barrier layer can be adapted from the embodiments and preferred forms of the <Method for Forming a Functional Layer> described above. Among these, a layer formed by applying and drying an oxygen barrier coating agent is preferred. The oxygen barrier coating agent can be adapted from the embodiments and preferred forms of the <Functional Coating Layer> described above. The amount of oxygen barrier layer to be applied is 0.5 to 15 g / m². 2 Preferably, 1 to 12 g / m 2 More preferably, 1.5-10 g / m 2 A more preferable option is a coating amount of 0.5 g / m² for the oxygen barrier layer. 2 As a result, the oxygen barrier properties and the appearance of the functional layer are further improved, 15g / m² 2 The following factors will further improve deadhold performance. The tensile strength of the oxygen barrier layer is less than 8 MPa, preferably 0.1 MPa or higher, more preferably 2 MPa or higher, and even more preferably 5 MPa or higher. Having the functional layer within the above range further improves the appearance and deadhold properties of the functional layer.

[0049] The oxygen barrier layer contains a resin (I), and preferably the resin (I) contains at least one selected from the group consisting of urethane resins (A), acrylic resins (B), styrene elastomer resins (C), and polysaccharide resins (D). Among these, polysaccharide resins (D) are preferred. When the oxygen barrier layer contains the above resin, the oxygen barrier properties, the appearance of the functional layer, and the deadhold properties are further improved. The oxygen barrier layer is preferably a layer comprising at least one material selected from the group consisting of urethane resin (A), acrylic resin (B), styrene elastomer resin (C), and polysaccharide resin (D), and an inorganic filler, and more preferably a layer comprising at least one material selected from the group consisting of urethane resin (A), acrylic resin (B), styrene elastomer resin (C), and polysaccharide resin (D), and an inorganic layered filler. When the oxygen barrier layer contains a combination of the above materials, the oxygen barrier properties, the appearance of the functional layer, and the deadhold properties are further improved.

[0050] The inorganic filler content is preferably 5 to 80% by mass, and more preferably 8 to 50% by mass, of 100% by mass of the oxygen barrier layer. When the inorganic filler content in the oxygen barrier layer is within the above range, the oxygen barrier properties, the appearance of the functional layer, and the dead-hold properties are further improved. Furthermore, the non-volatile content ratio of the resin to the inorganic filler in the oxygen barrier layer is preferably 9:1 to 5:5, and more preferably 8:2 to 6:4. When the non-volatile content ratio of the resin to the inorganic filler in the oxygen barrier layer is within this range, the oxygen barrier properties, the appearance of the functional layer, and the dead-hold properties are further improved.

[0051] <When the functional layer is an oil-resistant layer> An example of a functional layer used in the present invention is an oil-resistant layer. This oil-resistant layer is a layer in which, in the oil resistance evaluation described later, the measured area of ​​oil staining is less than 20% of the oil-stained area. The method for forming this oil-resistant layer can be adapted from the embodiments and preferred forms of the <Method for Forming a Functional Layer> described above. Among these, a layer formed by applying and drying an oil-resistant coating agent is preferred. The oil-resistant coating agent can be adapted from the embodiments and preferred forms of the <Functional Coating Layer> described above. Furthermore, the amount of oil-resistant layer to be applied is 0.5 to 15 g / m². 2 Preferably, 1 to 12 g / m 2 More preferably, 1.5-10 g / m 2 A more preferable option is a coating amount of 0.5 g / m² for the oil-resistant layer. 2 As a result, the water repellency and appearance of the functional layer are further improved, 15g / m 2 The following factors will further improve deadhold performance. The rupture strength of the oil-resistant layer is less than 8 MPa, preferably 0.1 MPa or higher, more preferably 1 to 7 MPa, and even more preferably 3 to 6 MPa. Having the functional layer within the above range further improves the appearance and dead-hold properties of the functional layer.

[0052] A preferred form of the oil-resistant layer can utilize the <water vapor barrier layer> described above.

[0053] <When the functional layer is a water-resistant layer> The functional layer used in the present invention is a water-resistant layer. This water-resistant layer is a layer that does not tear the substrate even after fewer than 30 cycles in the water resistance evaluation described later. The method for forming this water-resistant layer can be based on the embodiments and preferred forms of the <Method for Forming a Functional Layer> described above. Among these, a layer formed by applying and drying a water-resistant coating agent is preferred. Furthermore, the embodiments and preferred forms of the <Functional Coating Layer> described above can be based on the water-resistant coating agent. The amount of water-resistant layer to be applied is 0.5 to 15 g / m². 2 Preferably, 1.0 to 12 g / m 2 More preferably, 1.5-10 g / m 2 A more preferable option is a coating amount of 0.5 g / m² for the water-resistant layer. 2 This improves water resistance and the appearance of the functional layer, and the 15g / m² requirement is met. 2The following factors will further improve deadhold performance. The tensile strength of the water-resistant layer is less than 8 MPa, preferably 0.1 MPa or higher, more preferably 1 to 7 MPa, and even more preferably 3 to 6 MPa. Having the functional layer within the above range further improves the appearance and dead-hold properties of the functional layer.

[0054] The water-resistant layer contains a resin (I), which preferably contains at least one selected from the group consisting of urethane resin (A), acrylic resin (B), and styrene elastomer resin (C), with urethane resin (A) and / or acrylic resin (B) being particularly preferred. When the water-resistant layer contains the above resins, water resistance, the appearance of the functional layer, and deadhold properties are further improved. The water-resistant layer preferably comprises at least one material selected from the group consisting of urethane resin (A), acrylic resin (B), and styrene elastomer resin (C), and a hydrocarbon wax such as paraffin wax. When the water-resistant layer includes a combination of the above materials, water resistance, the appearance of the functional layer, and deadhold properties are further improved.

[0055] The content of resin (I) is preferably 60 to 90% by mass, and more preferably 70 to 90% by mass, of 100% by mass of the water-resistant layer. When the resin content in the water-resistant layer is within the above range, the water resistance, the appearance of the functional layer, and the dead hold properties are further improved.

[0056] The hydrocarbon wax content in the water-resistant layer is preferably 5 to 80% by mass, and more preferably 8 to 50% by mass, of 100% by mass of the functional layer. When the hydrocarbon wax content in the water-resistant layer is within the above range, water resistance, the appearance of the functional layer, and dead-hold properties are further improved. Furthermore, the non-volatile content ratio of the resin to the hydrocarbon wax in the water-resistant layer is preferably 9:1 to 5:5, and more preferably 9:1 to 7:3. When the non-volatile content ratio of the resin to the hydrocarbon wax in the water-resistant layer is within this range, water resistance, the appearance of the functional layer, and dead-hold properties are further improved.

[0057] <When the functional layer is a water-repellent layer> The functional layer used in the present invention is a water-repellent layer, which is a layer with a water repellency of R3 or higher as measured by JAPAN TAPPI No. 68. The method for forming the water-repellent layer can be adapted from the embodiments and preferred forms of the <Method for Forming a Functional Layer> described above. Among these, a layer formed by applying and drying a water-repellent coating agent is preferred. The water-repellent coating agent can be adapted from the embodiments and preferred forms of the <Functional Coating Layer> described above. The amount of water-repellent layer to be applied is 0.5 to 15 g / m². 2 Preferably, 1.0 to 12 g / m 2 More preferably, 1.5-10 g / m 2 A more preferable amount of water-repellent layer is 0.5 g / m². 2 As a result of meeting the above criteria, the water vapor barrier properties and the appearance of the functional layer are improved, and the density is 15g / m². 2 The following factors improve dead-hold performance. The tensile strength of the water-repellent layer is preferably 0.1 to 8 MPa, more preferably 0.5 to 6 MPa, and even more preferably 1 to 4 MPa. Having the functional layer within this range improves its appearance and dead-hold properties.

[0058] A preferred form of the oil-resistant layer can utilize the <water vapor barrier layer> described above.

[0059] <Preferred Embodiment of Functional Layer> Preferred commercially available resins (I) for use in the functional layer include, for example, acrylic resins (B): the Joncryl series from BASF Japan, such as Joncryl HPB1631, and the SEIKOAT series from Seikoh PMC, such as SEIKOAT NE-2260 and SEIKOAT PE-2273. Styrene elastomer resins (C): the SEPTON series from Kuraray, such as SEPTON2005 and SEPTON4033, and the ToughTec series from Asahi Kasei, such as ToughTec H1053 and ToughTec H1051.

[0060] [Anchor coat layer] The laminate of the present invention has a configuration having an anchor coat layer. The anchor coat layer needs to be located between the base material and the functional layer, and has the effect of improving the appearance and dead hold of the functional layer, and may have the same function as the functional layer. The breaking strength measured under condition (1) of the anchor coat layer is preferably 3 to 30 MPa, more preferably 4 to 25 MPa, even more preferably 8 to 23 MPa, and particularly preferably 12 to 20 MPa. When the breaking strength of the anchor coat layer is 3 MPa or more, it is possible to suppress the protrusion of paper base material fibers when folded, and when it is 30 MPa or less, it is possible to suppress cracking of the anchor coat layer when folded, thus further improving the appearance and dead hold of the functional layer. Furthermore, the breaking strain measured under condition (2) of the anchor coat layer is preferably 200% or more, more preferably 200 to 800%, and even more preferably 200 to 500%. When the breaking strain of the anchor coat layer is within the above range, the appearance and dead hold of the functional layer are further improved.

[0061] In this specification, it is preferable that the tensile strength of the functional layer and the tensile strength of the anchor coat layer satisfy the following formula 2. By satisfying the following formula 2, the functional layer and the anchor coat layer as a whole can improve adhesion to the substrate, suppression of paper fiber ejection when bent, and flexibility of the coating film, thereby further improving the appearance and dead hold of the functional layer. Equation 2: Breaking strength of functional layer [MPa] < Breaking strength of anchor coat layer [MPa] Furthermore, from the viewpoint of the appearance of the functional layer and deadhold properties, the difference between the tensile strength of the functional layer and the tensile strength of the anchor coat layer is preferably 1 to 25 MPa, more preferably 5 to 23 MPa, and even more preferably 10 to 20 MPa.

[0062] The resin (II) contained in the anchor coat layer preferably includes at least one selected from the group consisting of urethane resin (A'), acrylic resin (B'), styrene elastomer resin (C'), polyvinyl alcohol resin (E), and vinyl chloride resin (F), from the viewpoint of functional layer appearance and deadhold properties, with urethane resin (A') and / or acrylic resin (B') being more preferred. The amount of anchor coat layer applied is 0.5 to 10 g / m². 2 Preferably, 1.0 to 7 g / m 2 More preferably, 1.5 to 6.5 g / m 2 A more preferable option is an anchor coat layer application rate of 0.5 g / m². 2 As a result, the appearance of the functional layer is improved, 10g / m 2 The following factors improve dead-hold performance.

[0063] <Urethane resin (A')> The embodiments and preferred forms of the urethane resin (A') can be found by referring to the contents of <urethane resin (A)> described above. The urethane resin (A') is preferably used in combination with the vinyl chloride resin (F) described later, and the non-volatile content ratio of the urethane resin (A') to the vinyl chloride resin (F) in the anchor coat layer is preferably 90:10 to 40:60, and more preferably 80:20 to 50:50. When the non-volatile content ratio of the urethane resin (A') to the vinyl chloride resin (F) is within the above range, the appearance of the functional layer and the dead-hold properties are further improved.

[0064] <Acrylic resin (B')> The embodiments and preferred forms of the acrylic resin (B') can be found by referring to the contents of <acrylic resin (B)> described above.

[0065] <Styrene elastomer resin (C')> The embodiments and preferred forms of the styrene elastomer resin (C') can be found by referring to the contents of <styrene elastomer resin (C)> described above.

[0066] <Polyvinyl alcohol-based resin (E)> The polyvinyl alcohol-based resin (E) is a resin having vinyl alcohol units, and a resin containing units derived from ethylene is preferred. Examples of polyvinyl alcohol-based resins include polyvinyl alcohol resins and ethylene-vinyl alcohol copolymer resins. Among these, polyvinyl alcohol resins and / or ethylene-vinyl alcohol copolymer resins are preferred, and ethylene-vinyl alcohol copolymer resins are preferred.

[0067] The content of ethylene-derived units in the ethylene-vinyl alcohol copolymer resin is preferably 1 to 40 mol%, more preferably 3 to 20 mol%, and even more preferably 5 to 15 mol%. When the content of ethylene-derived units is within the above range, the oxygen barrier properties after bending are improved. The degree of polymerization of the polyvinyl alcohol-based resin is preferably 100 to 3,000, and more preferably 500 to 2,400. When it is within the above range, the oxygen barrier properties after bending are improved.

[0068] Polyvinyl alcohol-based resins may have functional groups. Examples of such functional groups include carbonyl groups and silanol groups. Furthermore, polyvinyl alcohol-based resins can be crosslinked. Examples of crosslinking agents include isocyanate-based crosslinking agents, epoxy-based crosslinking agents, melamine-based crosslinking agents, oxazoline-based crosslinking agents, and silane coupling-based crosslinking agents. Among these, oxazoline-based crosslinking agents and silane coupling-based crosslinking agents are preferred.

[0069] The degree of saponification of the polyvinyl alcohol-based resin is expressed by the following formula (Equation 6), and is preferably 80 mol% or more, more preferably 90 mol%, and even more preferably 95 mol%. When it is within the above range, the oxygen barrier properties are improved. (Formula 6) Degree of saponification: (Number of hydroxyl groups) / {(Number of hydroxyl groups) + (Number of acetate groups)} × 100 [mol%]

[0070] Commercially available polyvinyl alcohol-based resins include the Kuraray Poval R series (manufactured by Kuraray Co., Ltd., polyvinyl alcohol resin), Kuraray Eval L104B, F104B (manufactured by Kuraray Co., Ltd., ethylene-vinyl alcohol copolymer resin), and others.

[0071] <Vinyl chloride resin (F)> Vinyl chloride resin (F) is a resin having units derived from vinyl chloride monomer. Examples of vinyl chloride resin (F) include vinyl chloride-acrylic copolymer resin and vinyl chloride-vinyl acetate copolymer resin.

[0072] The mass-average molecular weight of the vinyl chloride resin (F) is preferably 10,000 to 100,000, and more preferably 30,000 to 70,000. The glass transition temperature of the vinyl chloride resin (F) is preferably 50 to 90°C, more preferably 55 to 85°C, and even more preferably 65 to 80°C. The hydroxyl value of the vinyl chloride resin (F) is preferably 10 to 120 mgKOH / g, more preferably 20 to 110 mgKOH / g, even more preferably 30 to 100 mgKOH / g, and particularly preferably 40 to 80 mgKOH / g. The content of units derived from vinyl chloride monomer is preferably 70 to 95% by mass of 100% by mass of the non-volatile content of the vinyl chloride resin (F).

[0073] Examples of commercially available vinyl chloride resins (F) include the Solvine A-type series and Solvine C-type series (manufactured by Shin-Etsu Chemical Co., Ltd.).

[0074] <Additives contained in the anchor coat layer> The nature and preferred form of additives included in the anchor coat layer can be determined by referring to the contents of the above-mentioned <additives included in the functional layer>.

[0075] <Method for forming the anchor coat layer> The method for forming the anchor coat layer can be adapted from the embodiments and preferred forms of the <Method for Forming a Functional Layer> described above. Among these, a layer formed by applying and drying an anchor coat agent is preferred.

[0076] <Anchor coating agent> The anchor coating agent can be prepared by uniformly mixing at least one resin (II) selected from the group consisting of urethane resin (A'), acrylic resin (B'), styrene elastomer resin (C'), and polyvinyl alcohol resin (E), a solvent, and additives as needed, using the mixing method described above for the <functional coating layer>.

[0077] <Preferred embodiment of the anchor coat layer> The anchor coating agent preferably contains resin (II). The selection of resin (II) is important for the anchor coating layer to satisfy the required breaking strength and breaking strain. Examples of resin (II) include acrylic resin (B'), such as the Joncryl series from BASF Japan, such as Joncryl HPB1631, and the SEIKOAT series from Seikoh PMC, such as SEIKOAT NE-2260 and SEIKOAT PE-2273. Examples of styrene elastomer resin (C') include the SEPTON series from Kuraray, such as SEPTON2005 and SEPTON4033, and the ToughTec series from Asahi Kasei, such as ToughTec H1053 and ToughTec H1051.

[0078] [Paper base material] Examples of paper substrates used in the laminate of the present invention include fine paper, coated paper, art paper, imitation paper, thin paper, thick paper, corrugated cardboard, etc. The basis weight of the paper substrate is 30 to 200 g / m². 2 Preferably, 40-150 g / m² 2 More preferably, 50-100 g / m 2 This is even more preferable. When the basis weight of the paper substrate is within the above range, the appearance of the functional layer and the deadhold properties are further improved. The thickness of the paper substrate is preferably 30 to 100 μm, and more preferably 40 to 70 μm.

[0079] [Ink layer] The laminate of the present invention may further have an ink layer. In this specification, the ink layer is a layer containing a colorant and used for decoration or aesthetic purposes; for displaying any picture, pattern, character, and symbol, etc., for purposes such as indicating contents, expiration date, and manufacturer or seller. The ink layer may have the same functions as the functional layer. The ink layer may further contain a resin. The ink layer can be formed, for example, using printing ink. Furthermore, the ink layer may be a single-layer or multi-layer structure, and may be printed on the surface. The mass per unit area of ​​the ink layer is 0.1 to 12 g / m². 2 Preferably, 0.5-6 g / m 2 More preferably, 1-3 g / m 2 That is even more preferable.

[0080] <Resin contained in the ink layer> Examples of resins included in the ink layer include urethane resin, cellulose resin, polyamide resin, rosin resin, ethylene-vinyl acetate copolymer resin, vinyl acetate resin, vinyl chloride-vinyl acetate copolymer resin, acrylic resin, styrene resin, styrene-maleic acid copolymer resin, and polyester resin. The resin can be used individually or in mixtures of two or more types.

[0081] <Coloring agent> Colorants include pigments and dyes. Among these, pigments are preferred. Pigments include organic pigments and inorganic pigments. Colorants can be used individually or in mixtures of two or more.

[0082] <Additives contained in the ink layer> The ink layer and printing ink may contain additives such as defoamers, fragrances, flame retardants, hydrocarbon waxes, thickeners, leveling agents, dispersants, curing agents, silane coupling agents, plasticizers, infrared absorbers, and ultraviolet absorbers, as needed. Preferably, the additives include at least one selected from the group consisting of hydrocarbon waxes and dispersants.

[0083] <Method of manufacturing printing ink> Printing inks can be produced by, for example, dispersing pigments, resins, and organic solvents in a disperser to create a pigment dispersion. Then, resins, additives, organic solvents, etc., are mixed into the obtained pigment dispersion. The dispersion process may be performed multiple times. Furthermore, the materials used in each step are arbitrary and can be substituted with other materials. Examples of dispersers include roller mills, ball mills, pebble mills, attritors, and sand mills.

[0084] <Formation of the ink layer> The ink layer can be formed, for example, by printing on a substrate using printing ink and then drying it. Gravure printing or flexographic printing are preferred printing methods. For example, the printing ink is diluted with a diluent solvent to a viscosity and concentration suitable for gravure printing, and then supplied to each printing unit, either alone or mixed with two or more other printing inks as needed, for coating. After that, the film is fixed by drying in an oven or the like to obtain the ink layer.

[0085] [Adhesive layer] The laminate of the present invention preferably has an adhesive layer. Methods for forming the adhesive, that is, methods for bonding (also called laminating) each layer, include, for example, extrusion lamination, dry lamination, and non-sol lamination. This further improves the adhesion between each layer. Examples of adhesive layers include olefin-based adhesives, acrylic-based adhesives, ethylene-vinyl acetate copolymer adhesives, dry lamination adhesives and non-sol lamination adhesives such as reaction products of polyols and isocyanate-based curing agents, imine-based anchor coating agents, butadiene-based anchor coating agents, and isocyanate-based anchor coating agents. Furthermore, the adhesive layer can be formed by extruding and laminating a thermoplastic resin. It is preferable that the adhesive layer is a reaction product of a polyol and an isocyanate-based curing agent.

[0086] [Intermediate material layer] The laminate of this application preferably has an intermediate substrate layer at any location. This improves the rigidity of the laminate. The intermediate substrate layer is preferably a plastic substrate mainly containing polyolefin resin as a raw material. Examples of plastic substrates include polyolefin resins such as low-density polyethylene (LDPE), linear low-density polyethylene (LLDPE), medium-density polyethylene (MDPE), high-density polyethylene (HDPE), ethylene-vinyl acetate copolymer, propylene homopolymer, and ethylene-propylene copolymer. Composite substrates of these are also acceptable. Furthermore, the intermediate substrate is more preferably made of the same material as the heat seal layer. Examples of the same material include combinations of polypropylene with polypropylene, polyethylene with polyethylene, etc. The film thickness of the intermediate substrate layer is preferably 10 to 100 μm, and more preferably 20 to 50 μm.

[0087] [Heat seal layer] The laminate of the present invention may further have a heat-seal layer. If the laminate of the present invention has a heat-seal layer, the heat-seal layer must be located on the surface opposite to the surface on the paper substrate that has the functional layer. In this specification, the heat-seal layer has the property of melting and fusing with heat, and may further have the same function as the functional layer. The heat-seal layer can be formed by coating or printing a heat-sealing agent containing a known heat-sealable resin such as a polyolefin resin such as polyethylene, a urethane resin, an acrylic resin, or an ethylene vinyl acetate copolymer resin. The heat-sealing agent may be coated by a known printing method such as gravure printing. Alternatively, a method of melt coating using an extruder or the like is also possible. The film thickness of the heat-seal layer is preferably 1 to 20 μm, and more preferably 3 to 10 μm.

[0088] [Method for manufacturing laminates] The present invention relates to a method for manufacturing a laminate having a paper substrate, an anchor coat layer, and a functional layer (excluding an ink layer) in this order, The process includes the steps of: applying an anchor coating agent to the paper substrate to form the anchor coating layer; and applying a functional coating agent to the anchor coating layer to form the functional layer. A method for manufacturing a laminate, comprising setting the breaking strength of the functional layer measured under the following condition (1) to less than 8 MPa. Condition (1): In accordance with JIS K 6251:2023, a dumbbell-shaped test specimen of type 3 with a thickness of 0.3 m and a width of 5 mm is prepared, a tensile test is performed at a tensile speed of 50 m / min, the load at fracture [N] is measured, and the fracture strength is calculated using the following formula 1. (Equation 1) Breaking strength [MPa] = (Load at break [N]) / (Cross-sectional area of ​​the test specimen [mm²]) 2 ]) In other words, the above manufacturing method comprises the steps of applying an anchor coating agent to a paper substrate to form the anchor coating layer, and applying a functional coating agent to the anchor coating layer to form the functional layer, characterized in that the breaking strength of the functional layer, as measured by the above measurement method, is less than 8 MPa.

[0089] <Process for forming the anchor coat layer> The process of forming the anchor coat layer can be carried out by utilizing the form and preferred form of the <Method for Forming the Anchor Coat Layer> described above.

[0090] <Process for forming the functional layer> The process of forming the functional layer can utilize the form and preferred form of the <Method for Forming a Functional Layer> described above.

[0091] [Packaging material] The laminate of the present invention is preferably used as a packaging material or as part of a packaging material, such as a flexible packaging package or a packaging bag. The packaging material may also be a packaging container.

[0092] [Example of an embodiment] Examples of embodiments of the present invention are given below. The present invention is not limited to the following.

[0093] <1> A laminate having, in order, at least a paper substrate, an anchor coat layer, and a functional layer (excluding the ink layer), The functional layer is at least one selected from the group consisting of a barrier layer, an oil-resistant layer, a water-repellent layer, and a water-resistant layer, and the functional layer comprises resin (I). A laminate in which the breaking strength of the functional layer measured under the following condition (1) is less than 8 MPa. Condition (1): In accordance with JIS K 6251:2023, a dumbbell-shaped test specimen of type 3 with a thickness of 0.3 m and a width of 5 mm is prepared, a tensile test is performed at a tensile speed of 50 m / min, the load at fracture [N] is measured, and the fracture strength is calculated using the following formula 1. (Equation 1) Breaking strength [MPa] = (Load at break [N]) / (Cross-sectional area of ​​the test specimen [mm²]) 2 ]) <2> The functional layer further includes an additive. <1> A laminate of [something]. <3> The aforementioned additive includes hydrocarbon waxes. <1> or <2> A laminate of [something]. <4> The breaking strength of the anchor coat layer measured under condition (1) is 3 MPa or more and 30 MPa or less. <1> ~ <3> Any of the laminated structures. <5> The rupture strength of the functional layer and the rupture strength of the anchor coat layer satisfy the following equation 2. <1> ~ <4> Any of the laminated structures. (Equation 2) Fracture strength of the functional layer < Fracture strength of the anchor coat layer <6> The difference between the tensile strength of the functional layer and the tensile strength of the anchor coat layer is 1 MPa or more and 25 MPa or less. <5> A laminate of [something]. <7> The fracture strain measured in the functional layer under the following condition (2) is 200% or more. <1> ~ <6> Any of the laminated structures. Condition (2): In accordance with JIS K 6251:2023, a dumbbell-shaped test specimen of type 3 with a thickness of 0.3 m and a width of 5 mm was prepared, and a tensile test was performed at a tensile speed of 50 m / min. The load at fracture [N] was measured, and the fracture strength was calculated using the following formula 3. Equation 3: Fracture strain [%] = {(gauge length at fracture) - (gauge length before tensile test)} / (gauge length before tensile test) × 100 Gauge markings distance before tensile test [mm]: 20 mm <8> Resin (I) comprises at least one resin selected from the group consisting of urethane resin (A), acrylic resin (B), styrene elastomer resin (C), and polysaccharide resin (D). <1> ~ <7> Any of the laminated structures. <9> The anchor coat layer contains at least one resin (II) selected from the group consisting of urethane resin (A'), acrylic resin (B'), and styrene elastomer resin (C'), polyvinyl alcohol resin (E), and vinyl chloride resin (F). <1> ~ <8> Any of the laminated structures. <10> A method for manufacturing a laminate having a paper substrate, an anchor coat layer, and a functional layer (excluding the ink layer) in this order, The process includes the steps of: applying an anchor coating agent to the paper substrate to form the anchor coating layer; and applying a functional coating agent to the anchor coating layer to form the functional layer. A method for manufacturing a laminate, comprising setting the breaking strength of the functional layer measured under the following condition (1) to less than 8 MPa. Condition (1): In accordance with JIS K 6251:2023, a dumbbell-shaped test specimen of type 3 with a thickness of 0.3 m and a width of 5 mm is prepared, a tensile test is performed at a tensile speed of 50 m / min, the load at fracture [N] is measured, and the fracture strength is calculated using the following formula 1. (Equation 1) Breaking strength [MPa] = (Load at break [N]) / (Cross-sectional area of ​​the test specimen [mm²]) 2 ]) [Examples]

[0094] The present invention will be described specifically and in detail below with reference to examples. The present invention is not limited to these examples. Note that "parts" refers to "parts by mass," and "%" refers to "percentage by mass."

[0095] <Acid value> The acid value is the number of milligrams of potassium hydroxide required to neutralize the free fatty acids, resin acids, etc., contained in 1 g of the sample, and was measured by the method described in JIS K 0070.

[0096] <Amine value> The amine value was determined by the amount of potassium hydroxide in milligrams equivalent to the amount of hydrochloric acid required to neutralize the amino groups contained in 1 g of the sample, and was measured in accordance with JIS K 0070. 0.5 to 2 g of the sample was accurately weighed (sample non-volatile content: Sg), and 50 mL of a methanol / methyl ethyl ketone = 60 / 40 (mass ratio) mixed solution was added to the weighed sample to dissolve it. Bromophenol blue was added to the resulting solution as an indicator, and the resulting solution was titrated with a 0.2 mol / L ethanolic hydrochloric acid solution (titer: f). The endpoint was defined as the point where the color of the solution changed from green to yellow, and the titration volume (A mL) at this point was used to determine the amine value using the following formula (Equation 11). (Formula 11) Amine value = (A × f × 0.2 × 56.108) / S [mgKOH / g]

[0097] <Weight average molecular weight> The weight-average molecular weight was determined by measuring the molecular weight distribution using a gel permeation chromatography (GPC) apparatus (HLC-8220, manufactured by Tosoh Corporation) and calculating the converted molecular weight using polystyrene as a standard substance. The measurement conditions are shown below. Columns: The following columns were used, connected in series. TSKgelSuperAW2500 manufactured by Tosoh Corporation TSKgel SuperAW3000 manufactured by Tosoh Corporation TSKgelSuperAW4000 manufactured by Tosoh Corporation TSKgelguard Column Super AWH manufactured by Tosoh Corporation Detector: RI (Differential Refractometer) Measurement conditions: Column temperature 40°C Eluent: Tetrahydrofuran Flow rate: 1.0mL / min

[0098] (Manufacturing of functional coating agents) <Manufacturing Example 1> Water vapor barrier coating agent A-1 20 parts of styrene-based elastomer resin (SIBSTAR 062T (styrene-isobutylene-styrene block copolymer), manufactured by Kaneka Corporation), 10 parts of hydrocarbon wax (Paraffin Wax 135, manufactured by Nippon Seiro Co., Ltd.), and 68 parts of solvent MCH (methylcyclohexane) (δd: 16.0, δp: 0) were heated while stirring at 80°C for 1 hour. After that, heating was stopped and stirring was continued until it returned to room temperature. Then, 2 parts of amorphous silica (Mizukasil P707, manufactured by Mizusawa Chemical Industries, Ltd.) were added and mixed and stirred to obtain water vapor barrier coating agent A-1.

[0099] <Manufacturing Example 2> Oil-resistant coating agent A-2 Oil-resistant coating agent A-2 was obtained by mixing and stirring 100 parts of water-based styrene acrylic resin (FILLHARMO GS500, manufactured by Toyo Chem Co., Ltd.) and 5 parts of water-based hydrocarbon wax emulsion (AQUACER497, manufactured by Big Chemie Japan Co., Ltd.).

[0100] <Manufacturing Example 3> Oil-resistant coating agent A-3 Oil-resistant coating agent A-3 was obtained by mixing and stirring 100 parts of water-based styrene acrylic resin (Joncryl HPB-1634, manufactured by BASF Japan) and 2 parts of amorphous silica (Mizukasil P707, manufactured by Mizusawa Chemical Industry Co., Ltd.).

[0101] <Manufacturing Example 4> Oil-resistant coating agent A-4 (Synthesis of urethane resin PU1) In a reactor equipped with a thermometer, stirrer, reflux condenser, and nitrogen gas inlet, 484.45 parts of poly(3-methyl-1,5-pentaneadipate)diol with a number average molecular weight of 2000, 24.18 parts of polyethylene glycol with a number average molecular weight of 2000, 21.56 parts of 2,2-dimethylolpropionic acid, and 138.24 parts of isophorone diisocyanate were reacted at a boiling point for 6 hours in 200 parts of methyl ethyl ketone to synthesize a terminal isocyanate prepolymer. The solution was then cooled to 40°C and 100 parts of acetone were added to obtain a terminal isocyanate prepolymer solution. Separately, 580.87 parts of the obtained terminal isocyanate prepolymer solution were gradually added at room temperature while stirring to a solution of 14.35 parts of 2-hydroxyethylethylenediamine, 4.78 parts of isophoronediamine, and 400 parts of acetone, and reacted at 50°C for 3 hours to obtain a solvent-type polyurethane resin solution. Next, 9.76 parts of 28% aqueous ammonia and 700 parts of deionized water were gradually added to the solvent-type polyurethane resin solution to neutralize it and make the resin water-soluble. Then, the solution was heated and the entire amount of methyl ethyl ketone and acetone was removed by distillation under azeotropic conditions. After that, water was added to adjust the viscosity and a polyurethane resin PU1 with an acid value of 30 mg KOH / g, a non-volatile content of 30%, a viscosity of 780 mPa·s, and a weight-average molecular weight of 35,000 was obtained.

[0102] (Manufacturing of functional coating agent A-4) 30.00 parts of the obtained polyurethane resin PU1, 0.10 parts of defoaming agent, 10.00 parts of isopropyl alcohol, and 29.90 parts of water were stirred and mixed, then kneaded in a sand mill. After thoroughly stirring and mixing 20.00 parts of polyurethane resin solution (PU01), 5.00 parts of isopropyl alcohol, and 10.00 parts of water, 5 parts of aqueous hydrocarbon wax emulsion (AQUACER497, manufactured by Big Chemie Japan) were mixed and stirred to obtain oil-resistant coating agent A-4.

[0103] <Manufacturing Example 5> Oil-resistant coating agent A-5 (Synthesis of urethane resin PU2) In a reactor equipped with a thermometer, stirrer, reflux condenser, and nitrogen gas inlet, 968.9 parts of poly(3-methyl-1,5-pentaneadipate)diol with a number average molecular weight of 4000, 24.18 parts of polyethylene glycol with a number average molecular weight of 2000, 21.56 parts of 2,2-dimethylolpropionic acid, and 138.24 parts of isophorone diisocyanate were reacted at a boiling point for 6 hours in 200 parts of methyl ethyl ketone to synthesize a terminal isocyanate prepolymer. The solution was then cooled to 40°C, and 100 parts of acetone were added to obtain a solvent solution of the terminal isocyanate prepolymer. Separately, 580.87 parts of the obtained terminal isocyanate prepolymer solution were gradually added at room temperature while stirring to a solution of 14.35 parts of 2-hydroxyethylethylenediamine, 4.78 parts of isophoronediamine, and 400 parts of acetone. The mixture was heated and reacted at 50°C for 3 hours to obtain a solvent-type polyurethane resin solution. Next, 9.76 parts of 28% aqueous ammonia and 700 parts of deionized water were gradually added to the solvent-type polyurethane resin solution to neutralize it and make the resin water-soluble. Then, the mixture was heated and the entire contents of the methyl ethyl ketone and acetone were removed by distillation under azeotropic conditions. After that, water was added to adjust the viscosity to obtain a polyurethane resin PU2 with an acid value of 30 mg KOH / g, a non-volatile content of 30%, a viscosity of 780 mPa·s, and a weight-average molecular weight of 50,000.

[0104] (Manufacturing of oil-resistant coating agent A-5) 30.00 parts of the obtained polyurethane resin PU2, 0.10 parts of defoaming agent, 10.00 parts of isopropyl alcohol, and 29.90 parts of water were stirred and mixed, then kneaded in a sand mill. After thoroughly stirring and mixing 20.00 parts of polyurethane resin solution (PU01), 5.00 parts of isopropyl alcohol, and 10.00 parts of water, 5 parts of aqueous hydrocarbon wax emulsion (AQUACER497, manufactured by Bic Chemie Japan) were mixed and stirred to obtain oil-resistant coating agent A-5.

[0105] <Manufacturing Example 6> Oxygen Barrier Coating Agent A-6 Oxygen barrier coating agent A-6 was obtained by mixing and stirring 100 parts of aqueous starch resin (RediFILM 5800, manufactured by Ingredion Japan) and 5 parts of glycerin solution (glycerin K-85, manufactured by Daishin Chemical Co., Ltd., 85% glycerin).

[0106] <Manufacturing Example 7> Water-resistant coating agent A-7 Water-resistant coating agent A-7 was obtained by mixing and stirring 100 parts of water-based acrylic resin (SEIKOAT PE-2273, manufactured by Seiko PMC Co., Ltd.), 100 parts of water-based acrylic resin (SEIKOAT QE-2128, manufactured by Seiko PMC Co., Ltd.), and 5 parts of water-based hydrocarbon wax emulsion (AQUACER497, manufactured by Big Chemie Japan Co., Ltd.).

[0107] <Manufacturing Example 8> Water-repellent coating agent A-8 Water-repellent coating agent A-8 was obtained by mixing and stirring 100 parts of water-based acrylic resin (SEIKOAT XP8812, manufactured by Seikoh PMC) and 5 parts of water-based hydrocarbon wax emulsion (AQUACER497, manufactured by Big Chemie Japan).

[0108] (Manufacturing of anchor coating agent that forms the anchor coating layer) <Manufacturing Example 9> Anchor Coating Agent B-1 (Synthesis of urethane resin PU3) In a four-necked flask equipped with a stirrer, thermometer, reflux condenser, and nitrogen gas inlet tube, 24.3 parts of a polyester polyol with a number-average molecular weight of 2,000, obtained by condensation polymerization of biomass sebaciate / adipic acid = 50 / 50 (mass ratio) and 1,3-propanediol / neopentyl glycol = 50 / 50 (mass ratio), 4 parts of isophorone diisocyanate, and 10 parts of ethyl acetate were charged and reacted at 120°C for 6 hours under a nitrogen stream. Then, 14 parts of propyl acetate were added and the mixture was cooled to obtain a solution of the terminal isocyanate prepolymer. Next, the solution of the obtained terminal isocyanate prepolymer was gradually added at room temperature while stirring to a solution prepared by mixing 1.7 parts of isophorone diamine (hereinafter also abbreviated as IPDA), 18 parts of ethyl acetate, and 28 parts of isopropyl alcohol (hereinafter also abbreviated as IPA). Then, the mixture was heated and reacted at 50°C for 1 hour to obtain a urethane resin PU3 with a non-volatile content of 30%, a mass-average molecular weight of 70,000, and an amine value of 5 mg KOH / g.

[0109] (Manufacturing of anchor coating agents) The obtained urethane resin PU3 was 20 parts, vinyl chloride-vinyl acetate resin solution was 10 parts, and silica particles (average particle size 5 μm, BET specific surface area 200 m²) were used. 2 1 part (1g) and 26 parts of mixed solvent (propyl acetate (NPAC) / IPA = 70 / 30 (mass ratio)) were stirred and mixed, then kneaded in a sand mill. After that, 20 parts of urethane resin solution, 19.7 parts of mixed solvent (propyl acetate / IPA = 70 / 30 (mass ratio)), 0.1 parts of polyalkyl vinyl ether (polyvinyl butyl ether copolymer, number average molecular weight 5,000, non-volatile content 20%), 3.0 parts of water, and 0.2 parts of quaternary ammonium salt (lauryltrimethylammonium chloride, non-volatile content 50%) were added and stirred and mixed to obtain anchor coating agent B-1.

[0110] <Manufacturing Example 10> Anchor Coating Agent B-2 (Synthesis of urethane resin PU4) In a reactor equipped with a thermometer, stirrer, reflux condenser, and nitrogen gas inlet, 96.89 parts of poly(3-methyl-1,5-pentaneadipate)diol with a number average molecular weight of 400, 24.18 parts of polyethylene glycol with a number average molecular weight of 2000, 21.56 parts of 2,2-dimethylolpropionic acid, and 138.24 parts of isophorone diisocyanate were reacted at a boiling point for 6 hours in 200 parts of methyl ethyl ketone while introducing nitrogen gas to synthesize a terminal isocyanate prepolymer. The solution was then cooled to 40°C and 100 parts of acetone were added to obtain a solvent solution of the terminal isocyanate prepolymer. Next, 580.87 parts of the obtained terminal isocyanate prepolymer solution were gradually added at room temperature while stirring to a solution prepared by mixing 14.35 parts of 2-hydroxyethylethylenediamine, 4.78 parts of isophoronediamine, and 400 parts of acetone. The mixture was heated and reacted at 50°C for 3 hours to obtain a solvent-type polyurethane resin solution. Next, 9.76 parts of 28% aqueous ammonia and 700 parts of deionized water were gradually added to the solvent-type polyurethane resin solution to neutralize it and make the resin water-soluble. Then, the solution was heated and all of the methyl ethyl ketone and acetone were removed by distillation under azeotropic conditions. After that, water was added to adjust the viscosity and a urethane resin PU4 with an acid value of 30 mg KOH / g, a non-volatile content of 30%, a viscosity of 780 mPa·s, and a weight-average molecular weight of 22000 was obtained.

[0111] (Manufacturing of anchor coating agents) 30.00 parts of the obtained polyurethane resin, 0.10 parts of the defoaming agent, 10.00 parts of isopropyl alcohol, and 29.90 parts of water were stirred and mixed, then kneaded in a sand mill. After that, 20.00 parts of polyurethane resin solution (PU01), 5.00 parts of isopropyl alcohol, and 10.00 parts of water were added and stirred and mixed to obtain anchor coating agent B-2.

[0112] <Manufacturing Example 11> Anchor Coating Agent B-3 Anchor coating agent B-3 was obtained by mixing and stirring 100 parts of aqueous styrene acrylic resin (Joncryl PDX-7616A, manufactured by BASF Japan) and 2 parts of amorphous silica (Mizukasil P707, manufactured by Mizusawa Chemical Industry Co., Ltd.).

[0113] <Manufacturing Example 12> Anchor Coating Agent B-4 Anchor coating agent B-4 was obtained by heating 6 parts of polyvinyl alcohol-based resin (Denka Poval B-05, manufactured by Denka Co., Ltd.) and 92 parts of a mixed solvent (water / IPA = 8 / 2) while stirring, and heating and stirring at 95°C for 1 hour.

[0114] <Manufacturing Example 13> Anchor Coating Agent B-5 (Synthesis of polylactic acid resin) In a four-necked flask equipped with a stirrer, thermometer, reflux condenser, and nitrogen gas inlet tube, 100 parts of M-lactide and 0.1 parts of octanol were charged and heated. At 180°C, 0.05 parts of 2-ethylhexanoate tin was added and ring-opening polymerization was carried out for 2 hours. Next, 0.08 parts of 116% strong phosphoric acid were added and residual lactide was removed under reduced pressure. Then, the non-volatile content was adjusted to 50% with ethyl acetate to obtain a polylactic acid resin solution with a weight-average molecular weight of 50,000. (Manufacturing of anchor coating agents) 33.3 parts of nitrocellulose (non-volatile content 30%, nitrogen content 11.5% to 12.2%, weight-average molecular weight 28,000 to 33,000), 39.9 parts of ethyl acetate, 20.0 parts of polylactic acid resin solution (non-volatile content 50%), 0.9 parts of Orgatic TC-100 (manufactured by Matsumoto Fine Chemicals, titanium chelate, non-volatile content 75%), 2.0 parts of diethylene glycol monobutyl ether, and 3.9 parts of Sunwax 131P (polyethylene wax, non-volatile content 40%) were stirred and mixed to obtain anchor coating agent B-5.

[0115] <Manufacturing Example 14> Anchor Coating Agent B-6 20 parts of styrene-based elastomer resin (SIBSTAR 062H (styrene-isobutylene-styrene block copolymer), manufactured by Kaneka Corporation) and 80 parts of solvent MCH (methylcyclohexane) (δd: 16.0, δp: 0) were heated while stirring, and heating and stirring were continued at 80°C for 1 hour. After that, heating was stopped and stirring was continued until it returned to room temperature. Then, 0.5 parts of amorphous silica (Mizukasil P707, manufactured by Mizusawa Chemical Industries, Ltd.) were added and mixed and stirred to obtain anchor coating agent B-6.

[0116] <Manufacturing Example 15> Anchor Coating Agent B-7 20 parts of styrene-based elastomer resin (SIBSTAR 103T (styrene-isobutylene-styrene block copolymer), manufactured by Kaneka Corporation) and 80 parts of solvent MCH (methylcyclohexane) (δd: 16.0, δp: 0) were heated while stirring, and heating and stirring were continued at 80°C for 1 hour. After that, heating was stopped and stirring was continued until it returned to room temperature. Then, 0.5 parts of amorphous silica (Mizukasil P707, manufactured by Mizusawa Chemical Industries, Ltd.) were added and mixed and stirred to obtain anchor coating agent B-7.

[0117] (Manufacturing of laminates) <Example 1> Laminate P-1 Paper base material (Nagoya bleached Ryuo, basis weight 70g / m²) 2 An anchor coat layer was formed on the glossy surface of a sheet of paper (manufactured by Daio Paper Corporation) by printing anchor coat agent B-1 using a gravure printing press equipped with a gravure plate with a plate depth of 30 μm at a printing speed of 30 m / min and an in-line oven at 80°C. Next, a functional layer was formed on the anchor coat layer by printing water vapor barrier coat agent A-1 twice using a gravure printing press equipped with a gravure plate with a plate depth of 60 μm at a printing speed of 30 m / min and an in-line oven at 80°C, thereby obtaining a laminate P-1 consisting of paper (substrate) / anchor coat layer / functional layer. The mass per unit area of ​​the anchor coat layer of laminate P-1 is 3 g / m² 2 The mass per unit area of ​​the functional layer is 7.0 g / m². 2 That was the case.

[0118] <Examples 2-21> Laminates P-2-P-21 Laminates P-2 to P-21 were obtained in the same manner as in Example 1, except that the anchor coating agent, functional coating agent, and lamination configuration were changed to achieve the laminate configurations shown in Table 1.

[0119] <Comparative Example 1> Laminate P-22 Paper base material (Nagoya bleached Ryuo, basis weight 70g / m²) 2An anchor coat layer was formed on the glossy surface of a sheet of paper (manufactured by Daio Paper Corporation) by printing anchor coat agent B-1 using a gravure printing press equipped with a gravure plate with a plate depth of 30 μm at a printing speed of 30 m / min and an in-line oven at 80°C. Next, an oil-resistant layer was formed on the anchor coat layer by printing FILLHARMO NS215 (water-based acrylic resin, manufactured by Toyo Chem Co., Ltd.) twice using a gravure printing press equipped with a gravure plate with a plate depth of 60 μm at a printing speed of 30 m / min and an in-line oven at 80°C, thereby obtaining a laminate P-22 consisting of paper (substrate) / anchor coat layer / functional layer. The mass per unit area of ​​the anchor coat layer of laminate P-22 is 3 g / m². 2 The mass per unit area of ​​the functional layer is 7.0 g / m². 2 That was the case.

[0120] <Comparative Example 2> Laminate P-23 (Method of manufacturing oxygen barrier coating agent) An oxygen barrier coating agent was obtained by heating 10 parts of polyvinyl alcohol-based resin (Exceval AQ-4104, manufactured by Kuraray Co., Ltd.) and 90 parts of a mixed solvent (water / IPA = 8 / 2) while stirring, at 95°C for 1 hour.

[0121] (Manufacturing method for laminate P-23) Paper base material (Nagoya bleached Ryuo, basis weight 70g / m²) 2 An anchor coat layer was formed on the glossy surface of a sheet of paper (manufactured by Daio Paper Corporation) by printing anchor coat agent B-1 using a gravure printing press equipped with a gravure plate with a plate depth of 30 μm at a printing speed of 30 m / min and an in-line oven at 80°C. Next, the obtained functional coating agent was printed five times on the anchor coat layer using a gravure printing press equipped with a gravure plate with a plate depth of 30 μm at a printing speed of 10 m / min and an in-line oven at 80°C to form a functional layer C-2, thereby obtaining a laminate P-23 consisting of paper (substrate) / anchor coat layer / functional layer. The mass per unit area of ​​the anchor coat layer of laminate P-23 is 3 g / m². 2 The mass per unit area of ​​the functional layer is 7.0 g / m². 2 That was the case.

[0122] <Rating> The resulting laminate was evaluated as follows. Water vapor barrier properties, oxygen barrier properties, oil resistance, water resistance, and water repellency were evaluated both before and after bending.

[0123] <Preparation of bending test samples> A 100mm x 100mm test piece was cut from the obtained laminate, and the piece was folded so that the intersection of the cross-shaped mountain fold was at the center of the surface where the functional layer was formed. A roll with a load of 500g was then passed back and forth five times to create a folded laminate sample, and various physical properties were evaluated. In the water repellency test, a folded laminate sample was prepared by folding the laminate so that the inner side of the surface where the functional layer was formed was folded vertically in a valley fold, and then running a roller with a load of 500g back and forth five times over it. Water droplets were then dropped onto the valley fold and the water repellency was evaluated by allowing the droplets to roll over the valley fold.

[0124] <Evaluation of water vapor barrier properties> The water vapor barrier properties were evaluated according to JIS Z0208:1976 (cup method) Method B (temperature 40℃±0.5℃, relative humidity 90%±2%). The obtained laminate samples were positioned so that the paper substrate side was on the low humidity side, and the water vapor transmission rate was measured and evaluated in the following four stages. Note that A, B, and C are within a range that does not pose a practical problem. A (Excellent): Water vapor transmission rate is 50 g / m³. 2 Less than (day) B (Good): Water vapor transmission rate is 50 g / m³ 2 ·day) or more, 100g / (m 2 Less than (day) C (acceptable): Water vapor transmission rate is 100 g / m³ 2 ·day) or more, 200g / (m 2 Less than (day) D (Not acceptable): Water vapor transmission rate is 200 g / m³ 2 (day) or more

[0125] <Oil Resistance Evaluation> One drop of salad oil was applied to the functional layer side of the laminated sample (center of the cross section in the bent sample) using a dropper. After 15 seconds, the salad oil was wiped off, and the presence or absence of oil stains was evaluated based on the following indicators. Note that A, B, and C represent a range that is not problematic for practical use. A (Excellent): No oil stains were found at all. B (Good): Oil-stained area is less than 10% of the oily area. C (Acceptable): The area stained with oil is 10% or more but less than 20% of the oily area. D (Not acceptable): Oil stains cover more than 20% of the oil-stained area.

[0126] <Oxygen barrier performance evaluation> The obtained laminate was cut into 100 mm squares, and the oxygen permeability was measured using a method compliant with JIS K 7126-2:2006, under measurement conditions of 23°C and 90% RH. The laminate was placed in an OC-TRAN oxygen permeability measuring device (manufactured by MOCON Corporation) with the functional layer facing the humidity-controlled side, and the oxygen permeability was measured. Values ​​A, B, and C are within a range that is practically acceptable. [Evaluation Criteria] A (Excellent): Oxygen permeability of 50 g / m³ 2 • Less than 24 hours B (Good): Oxygen permeability of 50 g / m³ 2 ·Over 24 hours, 100g / m 2 • Less than 24 hours C (acceptable): Oxygen permeability of 100 g / m³ 2 ·24h or more, 200g / m 2 • Less than 24 hours D (Not acceptable): Oxygen permeability of 200 g / m³ 2 • It is 24 hours or longer.

[0127] <Water resistance evaluation> For the functional layer surface of the obtained laminated sample (center of the cross section in the sample after bending), 0.1g of water was added to Kanakin No. 3, and the water resistance was evaluated using a JSPS testing machine by applying a load of 200g up to 100 times, with the number of cycles required for the paper substrate to tear being measured. A, B, and C represent ranges that are acceptable for practical use. [Evaluation Criteria] A (Excellent): No damage to the substrate even after more than 90 back-and-forth passes. B (Good): No damage to the substrate after 60 to 90 cycles. C (Acceptable): No damage to the substrate with 30 to 60 back-and-forth passes. D (Not acceptable): The base material will break if the number of back-and-forth cycles is less than 30.

[0128] <Water repellency evaluation> From the obtained laminate, a rectangular test piece measuring 300 mm x 200 mm was cut out. The water-repellent side of the test piece was placed facing upwards on a stand inclined at a 45° angle, and the water repellency was measured according to JAPAN TAPPI No. 68 and evaluated according to the following criteria. Note that A, B, and C represent a range that is acceptable for practical use. [Evaluation Criteria] A (Excellent): Water repellency R9~R10 B (Good): Water repellency R6~R8 C (acceptable): Water repellency R3~R5 D (not allowed): Water repellency R0~R2

[0129] <Functional layer appearance evaluation> For laminated samples after bending tests, the bending cross section of the functional layer was observed using a scanning electron microscope (SEM) with the bending cross section at the center of the observation field and at a magnification of 500x. The following criteria were used for evaluation. A, B, and C represent ranges that are acceptable for practical use. [Evaluation Criteria] A (Excellent): No paper fibers are seen to penetrate the coating agent when the paper is folded. B (Good): Paper fibers are only visible through the coating agent in the center of the cross shape. C (Acceptable): Paper fibers from the coating agent are visible at the center of the cross section and on one or two of the four sides (top, bottom, left, and right) extending from the center. D (Unacceptable): Paper fibers penetrate the coating agent at the center of the cross section and at three or more of the four sides (top, bottom, left, and right) from the center, resulting in a decrease in the functionality of the functional layer.

[0130] <Deadholding ability> A 100mm x 100mm test specimen was cut from the obtained laminate. The specimen was folded in half along the center of its edge so that the side with the functional layer was on the mountain fold side. A 500g roller was then passed back and forth five times, and after the load was stopped, the specimen was left to stand for one minute. The rise angle was evaluated according to the following criteria. A, B, and C represent ranges that are acceptable for practical use. [Evaluation Criteria] A (Excellent): The rise angle is less than 10°. B (Good): The rise angle is 10° or more and less than 25°. C (Acceptable): The rising angle is 25° or more and less than 50°. D (Not acceptable): The rising angle is 50° or more.

[0131] [Table 1]

[0132] [Table 2]

[0133] [Table 3]

[0134] As shown in Tables 1 to 3, Examples 1 to 21 are laminates having a paper base material, an anchor coat layer, and a functional layer in that order. Since the breaking strength of the functional layer is less than 8 MPa, each function of the functional layer remains practical even after bending, and the dead-hold properties are good. In particular, in Example 1, the breaking strength of the functional layer was 1.8 MPa and the breaking strength of the anchor coat layer was 18 MPa. Since the breaking strength of the anchor coat layer is greater than that of the functional layer, the laminate exhibited particularly excellent bending resistance and dead-hold properties. As described above, the present invention can provide a laminate with a functional layer that has excellent dead-hold properties and can be used in packaging materials with folds. On the other hand, in Comparative Example 1, the breaking strength of the functional layer was 8 MPa or higher, resulting in poor performance of each function of the functional layer after bending. In Comparative Example 2, the breaking strength was even higher, resulting in poor dead-hold properties. In Comparative Example 3, the laminated paper exhibited poor dead-hold properties.

Claims

1. A laminate having, in order, at least a paper substrate, an anchor coat layer, and a functional layer (excluding an ink layer), The functional layer is at least one selected from the group consisting of a barrier layer, an oil-resistant layer, a water-repellent layer, and a water-resistant layer, and the functional layer comprises resin (I). A laminate in which the breaking strength of the functional layer measured under the following condition (1) is less than 8 MPa. Condition (1): In accordance with JIS K 6251:2023, a dumbbell-shaped test specimen of type 3 with a thickness of 0.3 m and a width of 5 mm is prepared, a tensile test is performed at a tensile speed of 50 m / min, the load [N] at the time of fracture is measured, and the fracture strength is calculated using the following formula 1. (Equation 1) Breaking strength [MPa] = (Load at break [N]) / (Cross-sectional area of ​​the test specimen [mm²]) 2 ])

2. The laminate according to claim 1, wherein the functional layer further comprises an additive.

3. The laminate according to claim 2, wherein the additive comprises a hydrocarbon wax.

4. The laminate according to claim 1, wherein the breaking strength of the anchor coat layer measured under the above condition (1) is 3 MPa or more and 30 MPa or less.

5. The laminate according to claim 4, wherein the rupture strength of the functional layer and the rupture strength of the anchor coat layer satisfy the following formula 2. (Equation 2) Fracture strength of the functional layer < Fracture strength of the anchor coat layer

6. The laminate according to claim 5, wherein the difference between the tensile strength of the functional layer and the tensile strength of the anchor coat layer is 1 MPa or more and 25 MPa or less.

7. The laminate according to claim 1 or 2, wherein the fracture strain measured in the functional layer under the following condition (2) is 200% or more. Condition (2): In accordance with JIS K 6251:2023, a dumbbell-shaped test specimen of type 3 with a thickness of 0.3 m and a width of 5 mm was prepared, and a tensile test was performed at a tensile speed of 50 m / min. The load at fracture [N] was measured, and the fracture strength was calculated using the following formula 3. Equation 3: Breaking strain [%] = {(gauge length at break) - (gauge length before tensile test)} / (gauge length before tensile test) × 100 Distance between gauge marks before tensile test [mm]: 20 mm

8. The laminate according to claim 1 or 2, wherein the resin (I) comprises at least one resin selected from the group consisting of urethane resin (A), acrylic resin (B), styrene elastomer resin (C), and polysaccharide resin (D).

9. The laminate according to claim 1 or 2, wherein the anchor coat layer comprises at least one resin (II) selected from the group consisting of urethane resin (A'), acrylic resin (B'), and styrene elastomer resin (C'), polyvinyl alcohol resin (E), and vinyl chloride resin (F).

10. A method for manufacturing a laminate having a paper substrate, an anchor coat layer, and a functional layer (excluding the ink layer) in this order, The process includes the steps of: applying an anchor coating agent to the paper substrate to form the anchor coating layer; and applying a functional coating agent to the anchor coating layer to form the functional layer. A method for manufacturing a laminate, comprising setting the breaking strength of the functional layer measured under the following condition (1) to less than 8 MPa. Condition (1): In accordance with JIS K 6251:2023, a dumbbell-shaped test specimen of type 3 with a thickness of 0.3 m and a width of 5 mm is prepared, a tensile test is performed at a tensile speed of 50 m / min, the load [N] at the time of fracture is measured, and the fracture strength is calculated using the following formula 1. (Equation 1) Breaking strength [MPa] = (Load at break [N]) / (Cross-sectional area of ​​the test specimen [mm²]) 2 ])

Citation Information

Patent Citations

  • Bending resistance agent and laminate

    JP7588264B1